Preparation of a water-soluble preparation in the form of a powdery solid from Ilex guayusa Loes. - Luna-Fox, Sting Brayan (2023)
The research consisted of preparing a water-soluble product in the form of a pulverulent solid from the aqueous Ilex guayusa Loes., leaves extract, for which it was considered a priority to maximize the content of caffeine and polyphenols. Reflux decoction was used as the solid-liquid extraction method; the best conditions to extract the greatest amount of caffeine and polyphenols were with 15 g of guayusa leaves in 100 mL of distilled water, boiling for 30 min. Using ultraviolet-visible spectrophotometry, the amount of caffeine and total polyphenols was quantified, and concentrations of 71.7 and 55.76 mg·L-1 were obtained, respectively. Finally, the spray drying technology was applied to obtain the water-soluble powdery solid. For the characterization of the product, solubility tests were carried out, which resulted in a dissolution time when hot (close to boiling temperature) of less than 30 seconds and when cold (16 °C ± 2 °C) of less than 3 min. The pH and the total ash content were determined, which were 5.50 and 13.87%, respectively. From the microbiological evaluation it was found that the product was free of mesophilic aerobic microorganisms. The copper, zinc and iron content, determined by atomic absorption spectrophotometry, was 12.35, 234.50 and 19.35 mg·kg-1, correspondingly; lead was not detectable. The results obtained were consistent with the NTE INEN 1122:2013 regulation related to the requirements of soluble coffee obtained by spray drying. This research lays the foundations for the industrial development of a water-soluble product based on an aqueous extract of I. guayusa leaves, rich in caffeine and polyphenols.